Real-time acoustic energy harvesting in tunable frequencies via metasurface fabricated by additive manufacturing - Chi, Mingxiang (2023)
This paper demonstrates an acoustic metasurface for energy harvesting at tunable frequencies. The support structure of the metasurface was fabricated by additive manufacturing. The acoustic absorption coefficient and sound transmission loss of the metasurface can be tuned by optimization of various structural parameters, such as mass, mass size, prestress, membrane thickness, and array arrangement. The impedance tube was used to test the sound absorption ability of the fabricated metasurface, and the numerical simulation agreed well with the experiment, with a minimum acoustic absorption coefficient at ∼400 Hz. A PZT structure was designed and integrated into the acoustic metasurface, transforming the absorbed acoustic energy into electrical energy. Real-time acoustic energy harvesting was realized, and the peak voltage of 1.469 V was successfully monitored under the excitation of 410 Hz. For future applications, the energy harvesting efficiency can be further increased by improving the isolation components of the whole system.